2023
DOI: 10.31955/mea.v7i2.3091
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Intellectual Capital Dan Implementasi Good Corporate Governance Terhadap Peningkatan Kinerja Keuangan

Anggraini Triaski Ramadhani,
Erna Sulistyowati

Abstract: Penelitian ini bertujuan untuk memahami pengaruh intellectual capital dan implementasi good corporate governance terhadap peningkatan performa finansial perusahaan di sektor teknologi yang tercatat di Bursa Efek Indonesia selama 3 tahun penelitian pada periode 2019-2021. Metode analisis Partial Least Squares (PLS) yang berfokus pada aspek kuantitatif digunakan pada penelitian ini. Dilaksanakan penggunaan teknik yang dikenal sebagai purposive sampling. Dari hasil penelitian ini, terungkap bahwa intellectual cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…However, this study found that intellectual capital only sometimes significantly impacts financial performance. This is in line with previous research, stating that intellectual capital and the implementation of good corporate governance do not significantly affect financial performance (Hermanto et al, 2021;Ramadhani & Sulistyowati, 2023). Meanwhile, based on the similar research which stated that intellectual capital does not influence company value but significantly affects financial performance (Gunawan & Tartila, 2017;Nugroho et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, this study found that intellectual capital only sometimes significantly impacts financial performance. This is in line with previous research, stating that intellectual capital and the implementation of good corporate governance do not significantly affect financial performance (Hermanto et al, 2021;Ramadhani & Sulistyowati, 2023). Meanwhile, based on the similar research which stated that intellectual capital does not influence company value but significantly affects financial performance (Gunawan & Tartila, 2017;Nugroho et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Based on previous research stated that the impact of intellectual capital and good corporate governance on company performance (Hidayat et al, 2021;Ramadhani & Sulistyowati, 2023). This is similar to the research that will be conducted, which also wants to measure the effect of intellectual capital on company performance.…”
Section: Introductionmentioning
confidence: 85%